Individual Variation in Responding to Leader–Member Exchange Differentiation: The Moderating Roles of Internal Locus of Control and Self-Efficacy - Paik, Yonjeong; Lee, Eun Suk (Journal of Leadership and Organizational Studies, 2022)
This study examines how differentiation in leader–member exchange relationships (LMXD) provokes different individual responses depending on personal dispositions—internal locus of control and self-efficacy. Further, we identify three types of individual behavioral responses to LMXD: in-role and extra-role performance as self-focused responses, impression management toward the leader as a leader-focused response, and social undermining of coworkers as a coworker-focused response. Analysis of data from a survey conducted in South Korea demonstrates cross-level interaction effects between LMXD and the two dispositional variables on these behavioral responses of individuals. Specifically, LMXD is more positively related to in-role and extra-role performance and impression management toward the leader for individuals high than low in internal locus of control and for individuals high than low in self-efficacy. However, the cross-level interaction effects are not supported regarding social undermining of coworkers. Theoretical and practical implications of the findings are discussed.
Keywords: impression management; internal locus of control; LMX differentiation; self-efficacy; social undermining